Recent Advances on the Application of Electrocyclic Reactions in Complex Natural Product Synthesis - Bian, Ming; Li, Lekai; Ding, Hanfeng (Synthesis, 2017)
The electrocyclic reaction is one of the most powerful tools for the construction of complex polycyclic scaffolds in a highly stereocontrolled fashion. In this review, recent advances in its application in the total synthesis of representative natural products are discussed, with the aim of providing a complement to existing reviews.1 Introduction2 4π Electrocyclization2.1 Neutral 4π Electrocyclization2.2 Cationic 4π Electrocyclization3 6π Electrocyclization3.1 All-Carbon 6π Electrocyclization3.2 Oxa-6π Electrocyclization3.3 Aza-6π Electrocyclization3.4 Retro-6π Electrocyclization4 8π Electrocyclization5 Conclusion and Outlook
Keywords: electrocyclic reactions; conjugated alkenes; natural products; total synthesis; cascade reactions